2021
DOI: 10.1177/1533033820988525
|View full text |Cite
|
Sign up to set email alerts
|

LINC01232 Sponges Multiple miRNAs and Its Clinical Significance in Pancreatic Adenocarcinoma Diagnosis and Prognosis

Abstract: Background: Long noncoding RNAs have been demonstrated to play important roles in different kinds of human malignancy. The purpose of this study was to evaluate the diagnostic and prognostic value of long intergenic non-protein coding RNA 1232 (LINC01232) in patients with pancreatic adenocarcinoma (PAAD) and further explore the clinical significance of the potential miRNAs that might be sponged by LINC01232. Methods: The potential target miRNAs that might be sponged by LINC01232 were analyzed using bioinformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Non-coding RNAs (ncRNAs) are key components of the transcriptome and play important roles in both normal biological activity and pathological processes, such as viral infection and tumorigenesis [ 19 ]. Previous studies have demonstrated that LINC01232 exerts an oncogenic role in numerous types of tumors [ 8 , 9 ]. In this study, we found that the expression of LINC01232 was upregulated in STAD tissues and gastric cancer lines, indicating that LINC01232 may be a functional gene and a molecular target for clinical treatment of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-coding RNAs (ncRNAs) are key components of the transcriptome and play important roles in both normal biological activity and pathological processes, such as viral infection and tumorigenesis [ 19 ]. Previous studies have demonstrated that LINC01232 exerts an oncogenic role in numerous types of tumors [ 8 , 9 ]. In this study, we found that the expression of LINC01232 was upregulated in STAD tissues and gastric cancer lines, indicating that LINC01232 may be a functional gene and a molecular target for clinical treatment of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA has a variety of biological functions in all stages of cancer development, including cell development and immunity, cell proliferation and differentiation, and apoptosis regulation [ 7 ]. Previous evidence has indicated that long intergenic nonprotein-coding RNA 1232 (LINC01232) exerts an oncogenic role in numerous types of tumors, including pancreatic adenocarcinoma, esophageal squamous cell carcinoma, et al , [ 8 , 9 ]. In this study, we pre-analyzed the expression of LINC01232 in TCGA database using the GEPIA online tool.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the TCGA database and clinical tissues showed that the expression of LINC01232, TM9SF2, and EIF4A3 is upregulated in PAAD. LINC01232 is an lncRNA that is highly expressed in PAAD and has been associated with poor prognosis ( 47 ). However, no correlation between EIF4A3 and LINC01232 expression has been identified, suggesting that EIF4A3 might be recruited by LINC01232.…”
Section: Eif4a3 Acts As An Oncogene In Malignant Tumorsmentioning
confidence: 99%
“…As a novel lncRNA, long intergenic non‐protein coding RNA 1232 (LINC01232) has been validated to exert function in the development and progression of human cancers, such as pancreatic cancer (Du et al., 2021; Li et al., 2019; Meng et al., 2020), esophageal squamous cell carcinoma (Zhao et al., 2020), and gastric cancer (Liu et al., 2021). Nonetheless, the specific function of LINC01232 in BC remains unclear.…”
Section: Introductionmentioning
confidence: 99%